PENGARUH LINGKUNGAN BELAJAR, BIAYA PENDIDIKAN DAN PEMBELAJARAN DARING TERHADAP MOTIVASI BELAJAR MAHASISWA AKUNTANSI UNIVERITAS ISLAM MALANG PADA MASA PANDEMI COVID-19 (Studi Empiris pada Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Nais Aprilia; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2022)
This research objective is to know the influence of the learning environment, the cost of education, and online learning on the learning motivation of accounting students at the Islamic University of Malang during the Covid-19 pandemic. This research uses primary data with the criteria of students of the accounting study program, Faculty of Economics and Business, the University of Islam Malang, who have carried out online learning for at least two semesters. The method of collecting data through a questionnaire through google form using a Likert scale of 1-4. The number of samples used in this study was 90 students, with a data analysis method of multiple linear regression analysis. The results of the research test prove that the Learning Environment, Tuition Fees, and online learning have a positive and significant effect on the learning motivation of accounting students at the Islamic University of Malang during the Covid-19 pandemic.Keywords: Learning environment, education costs, online learning, learning motivation